Autologous blood pleurodesis: A good choice in patients with persistent air leak - Cobanoglu Ufuk; Melek Mehmet; Edirne Yesim (Annals of Thoracic Medicine, 2009)
Aim: The study compares the efficiency, side effects and complications of autologous blood pleurodesis with talcum powder and tetracycline. Materials and Methods: This prospective study evaluated 50 patients with persistent air leak resulting from primary and secssondary spontaneous pneumothorax between February 2004 and March 2009. The patients inclussded 32 (64.0%) males and 18 (36.0%) females with a median age of 39 years (range 14-69 years). All cases had persistent air leak of more than seven days. Pleurodesis was performed using autologous blood in 20 (40.0%) patients, talc powder in 19 (38.0%) patients and tetracycline in 11 (22.0%) patients through a chest tube. Air leak cessation times after pleurodesis, side effects and pulmonary function tests (PFT) in the first and third months were measured. Results: Recurrent primary spontaneous pneumothorax was the cause of persistent air leak in all cases. Air leaks were expiratory only in 54.0% of cases. We obtained a success rate of 75.0% using autologous blood, 84.2% using talc powder and 63.6% using tetracycline. Mean air leak termination interval was significantly (P < 0.001) shorter in patients treated with autologous blood in comparison to talc powder and tetracycline. We observed a significant (P < 0.05) decline in PFT in patients treated with talc powder compared with tetracycline and autologous blood. Vital capacity, FVC and FEV1 were significantly lower in patients treated with tetracycline compared with autologous blood. Conclusion: This study shows that autologous blood pleurodesis compared to talc powder and tetracycline is related with shorter leak cessation time and less pulmonary function decline in patients with persistent air leak. We think further randomized clinical trials of pleurodesis as treatment could increase its use in thorax surgery by demonstrating the safety and the efficacy of this procedure.